Planting geometry as a pre‐screening technique for identifying CO2 responsive rice genotypes: a case study of panicle number. Issue 3 (22nd May 2014) - Shimono, Hiroyuki; Ozaki, Youhei; Jagadish, Krishna S. V.; Sakai, Hidemitsu; Usui, Yasuhiro; Hasegawa, Toshihiro; Kumagai, Etsushi; Nakano, Hiroshi; Yoshinaga, Satoshi
<x xml:space="preserve">Abstract</x> Identifying CO2 responsive genotypes is a major target for enhancing crop productivity under future global elevated atmospheric CO2 concentration ([CO2]). However, [CO2]‐fumigation facilities are extremely expensive and are not easily accessible, and are limited in space for large‐scale screening. Hence, reliable donors for initiating [CO2]‐responsive breeding programs are not in place for crops, including rice. We propose a simple and novel phenotyping method for identifying [CO2]‐responsive genotypes, and quantify the responsiveness to low planting density over 4‐year trials across both temperate and tropical conditions. Panicle number per plant is the key determinant of grain yield and hence was the focus trait across all our trials. In temperate climate, a 3‐season field screening using 127 diverse rice genotypes and employing two planting densities (normal and low density) was conducted. Two japonica genotypes were selected based on their higher responsiveness to low planting density as candidates for validating the proposed phenotyping protocol as a pre‐screen for [CO2]‐responsiveness. The approach using the two selected candidates and three standard genotypes was confirmed using a free‐air CO2 enrichment facility and temperature gradient chambers under elevated [CO2]. In tropical climate, we grew three rice cultivars, previously identified for their [CO2]‐responsiveness, at two planting densities. The experiments provided confirmation that responsiveness to low planting density was correlated with that of [CO2]‐responsiveness across both the temperate and tropical conditions. The planting density would be useful pre‐screening method for testing large panels of diverse germplasm at low cost complemented by available CO2‐control facilities for final validation of candidates from the pre‐screens.